(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
There are a number of positive ideals about Mwalimu Julius Nyerere in the literatures. His ideals includes among others his devotion for peace, security, unity and democracy. However, the ideals do not limit the visibility of his negative traits. This paper specially examines the criticisms against Nyerere. The paper looks at the portrayal of Nyerere in number literatures from his critics. It examines the literatures against Nyerere in number of issues including his role in the decolonization struggle, the situation of democracy and individual freedom during his reign and his position towards Islamic religion and Zanzibar revolution. The paper establishes that most of criticisms against Nyerere are not refuted because supporters and critics talk about different things. Whereas his supporters put forward his role in building the nation, critics focus his in his economic failure and deprivation of individual freedom in Tanzania.